Rigorous Thinking in Mathematics Modelling for Slow Learners. Issue 1 (January 2021) - Setyawan, F; Andriyani; Handayani, Tri Kinasih; Ratih, Koesoemo; Sutopo, Anam; Rusli, Tri Indah; Alfiany, Nur Rizky
Abstract: Rigorous questions in discussion learning method plays a dominant role in the successful delivery of lessons for slow learners at higher education. This study aims to propose a framework to achieve good critical thinking for slow learners through Rigorous Mathematics computational Thinking (RMcT) model. This study used qualitative approach to describe slow learner's critical thinking by using RMcT model. The instruments used in this study were test instrument, critical thinking questionnaire, and interview guideline as supporting instrument to describe slow learner's critical thinking through RMcT model. The subjects were college students in mathematics modelling course in mathematics education department. Based on critical thinking test results, slow learners could divide variable used in mathematics modelling. Based on questionnaire results, slow learner students build their own understanding and solve the problem based on their experience while answering the given question during learning process. In addition, the interview they feel that the instructor can mediated the problem by giving analogy to the other material. In summary, RMcT could mediate slow learner's critical thinking as its characteristics (by using Rigorous questions). Findings are useful for designers, service providers and policy makers of special needs higher school when implementing teaching strategy to mediated real-life problems into mathematics modelling for slow learners.